2015
DOI: 10.1007/s40475-015-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis: New Research Developments in Pathophysiology, Pathogenesis, and Virulence Factors

Abstract: Giardia duodenalis is a very common, ubiquitous, intestinal protozoan parasite infecting animals and humans. Of the eight distinct genetic assemblages known to date, assemblages A and B are infectious to humans. Giardia is the most commonly recognized cause of traveller's diarrhea. Giardiasis impairs weight gain and is responsible for a variety of extraintestinal and post-infectious complications, including postinfectious irritable bowel syndrome, chronic fatigue, failure to thrive, and cognitive impairment. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 91 publications
0
28
0
4
Order By: Relevance
“…Our understanding of the pathophysiology and immunity in giardiasis is drastically improving, yet discrepancies in study results persist and much remains to be learned [ 23 , 24 , 25 , 26 ]. Several parasites are known to affect various aspects of their host’s pro-inflammatory responses [ 27 , 28 ], and recent findings indicate that Giardia actively modulates host inflammatory responses (as referenced below).…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the pathophysiology and immunity in giardiasis is drastically improving, yet discrepancies in study results persist and much remains to be learned [ 23 , 24 , 25 , 26 ]. Several parasites are known to affect various aspects of their host’s pro-inflammatory responses [ 27 , 28 ], and recent findings indicate that Giardia actively modulates host inflammatory responses (as referenced below).…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of acute diarrhea in giardiasis implicates increased rates of enterocyte apoptosis, disruption of the intestinal barrier function, activation of host lymphocytes, CD8 + lymphocyte-mediated shortening of brush border microvilli with or without coinciding villous atrophy, crypt hyperplasia, deficiency of disaccharidases, intestinal malabsorption, anion hypersecretion, and increased intestinal transit (Müller, von Allmen, 2005;Buret et al, 2015).…”
Section: Giardia and Giardiasismentioning
confidence: 99%
“…It has been suggested that the intestinal microbiota composition can potentially interfere in the process of G. lamblia infection. Findings from ongoing research indicate that the post-infectious effects of giardiasis may be due to microbiota dysbiosis induced by the parasite during the acute phase of infection (Buret et al, 2015). Keselman et al (2016) found that the disruption of the intestinal microbiota through antibiotic treatment for G. lamblia limited the disaccharidase deficiency, prevented pathological CD8 + T cell activation, and also did not change the numbers of CD4 + T cells in the lamina propria and the activation of T cell receptor-expressing intraepithelial lymphocytes (IEL) found in giardiasis.…”
Section: Giardia and Intestinal Microbiome Associationmentioning
confidence: 99%
“…Infections can result in subclinical disease with patients exhibiting little, if any, sign of the infection or can produce severe cramps, nausea, and diarrhea. Nutrient malabsorption can occur in patients with subclinical disease, as well as those experiencing acute symptoms, and Giardia infection has been correlated to physical and cognitive developmental defects in children in several studies (5,6). The mechanisms involved in both control of the infection and the production of symptoms are not well understood, although immune responses are considered important for both.…”
Section: Cd197mentioning
confidence: 99%